2010
DOI: 10.1093/jac/dkp479
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hepatitis B virus genotype and viraemia in HIV-infected patients with chronic hepatitis B in Europe

Abstract: Background: Both natural history and treatment outcome of hepatitis B virus (HBV) infection are influenced by genotypes and viral load. Information about factors determining HBV genotype distribution and viraemia in HIV/HBV-co-infected patients is scarce.Methods: All HIV-positive patients living in Europe and Argentina recruited in EuroSIDA (1994EuroSIDA ( -2006 were tested for serum HBV surface antigen (HBsAg). Chronic carriers were further characterized virologically at one central laboratory. Variables infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 37 publications
5
23
0
1
Order By: Relevance
“…This shows that wild-type HBV seems to remain particularly frequent in the setting of HIV infection, which is not the case in HBV mono-infected patients. As HBV assessment becomes more frequent, it appears that the HBV genotype is often type A in HIV positive patients, as previously observed [4,14], which is not the case in HIV negative ones (where the D genotype prevails). This probably reflects the difference between HIV positive and HIV negative patients concerning geographic origin [15].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This shows that wild-type HBV seems to remain particularly frequent in the setting of HIV infection, which is not the case in HBV mono-infected patients. As HBV assessment becomes more frequent, it appears that the HBV genotype is often type A in HIV positive patients, as previously observed [4,14], which is not the case in HIV negative ones (where the D genotype prevails). This probably reflects the difference between HIV positive and HIV negative patients concerning geographic origin [15].…”
Section: Discussionsupporting
confidence: 53%
“…In most Western countries, chronic hepatitis B (CHB) is frequently associated with HIV infection, with a 5-to 10-fold greater prevalence compared to the non HIV population, since 5% to 10% of HIV positive patients are chronically infected with HBV [1][2][3][4]. The impact and the perception of HBV-HIV co-infection have evolved over time, from a negligible problem overshadowed by the AIDS related illnesses, towards a genuine risk factor for increased morbidity and mortality [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, predominant genotype A HBV coinfection in HIV-seropositive MSM populations has also been reported in European and South American countries (20,26,33), suggesting that the prevailing genotype A in HIV-seropositive MSM has become a worldwide HBV epidemic. Regarding HBV genotypes in the HIV-negative population in Japan, genotype A has been increasing, but the major HBV genotype is still C, with genotype A remaining at 3.5% nationwide and 2.1% in the Tokai area, which includes Nagoya city (9).…”
Section: Discussionmentioning
confidence: 88%
“…A reduction and even elimination of HBsAg is thought to occur mainly by the immune-mediated clearance of HBV-infected cells, rather than by nucleoside-analogue-induced inhibition of the viral polymerase, supporting the importance of a competent immune system for viral control (5). The negative effect of low CD4 counts on HBV-related parameters could be shown previously in HBV/HIV co-infected patients, in whom it was associated with detectable HBV viremia (20). Patients with a final CD4 count > 350 cells/lL also had a more pronounced HBsAg decline.…”
Section: Analysis Of Hbsag In Hbv/hiv Co-infected Patientsmentioning
confidence: 67%
“…Also, patients showing rapid on-treatment HBsAg declines are more likely to achieve serological end-points like HBeAg seroconversion or HBsAg loss, and virological endpoints including sustained viral suppression. While it could be shown that low CD4 counts are a risk factor for the persistence of HBV-DNA in HBV/HIV-co-infected subjects (3,12), data on quantitative HBsAg in special cohorts are scarce, and could help identify the parameters associated with HBsAg declines (14,20,21). Here the longitudinal course of HBsAg in 51 HBV/HIV co-infected patients followed for a mean of approximately 3.5 y is reported.…”
Section: Discussionmentioning
confidence: 97%